2008
DOI: 10.1108/03074350810874055
|View full text |Cite
|
Sign up to set email alerts
|

Tenure, firm's performance, and CEO's compensation

Abstract: Purpose -The purpose of this paper is to assess the association between Chief Executive Officer (CEO) tenure, compensation, and firm's performance. Design/methodology/approach -The paper compares the influence firms' performance on CEOs' cash and total compensation based on the length of tenure. It also examines pay-performance relationship for new CEOs vs those serving their last year in such positions. Findings -The firm size appears to be a significant explanatory variable for CEOs' cash and total compensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
(19 reference statements)
2
29
0
1
Order By: Relevance
“…The coefficient is economically important (0.139) implying that an increase in the CEO's tenure by one year will increase executives' rewards by roughly 14%. This finding stands in line with the previous evidence of Nourayi and Mintz (2008). Moreover, the estimate for the CEO ownership is positive and statistically significant at the 1% level.…”
Section: Regression Resultssupporting
confidence: 92%
“…The coefficient is economically important (0.139) implying that an increase in the CEO's tenure by one year will increase executives' rewards by roughly 14%. This finding stands in line with the previous evidence of Nourayi and Mintz (2008). Moreover, the estimate for the CEO ownership is positive and statistically significant at the 1% level.…”
Section: Regression Resultssupporting
confidence: 92%
“…There is substantial evidence in earlier studies that firm size and CEO compensation are positively related (e.g., Finkelstein & Hambrick, 1989;Lambert et al, 1991;Canarella & Gasparyan, 2008;Nourayi & Mintz, 2008). Based on the previous studies, we formulate the following hypothesis.…”
Section: Ceo Compensation and Firm Sizementioning
confidence: 98%
“…While some studies use firm size as a control variable, others consider it as an explanatory variable. Nourayi and Mintz (2008) and Ghosh (2006) identified a positive effect of firm size on CEO compensation.…”
Section: Ceo Compensation and Firm Sizementioning
confidence: 99%
“…Nourayi and Mintz [16] indi-cate that the firm size appears to be a significant explanatory variable for executive cash compensation. Early and Cleverley [12] and Langer [13] also describe that the firm size influences the CFO compensation.…”
Section: Firm Sizementioning
confidence: 99%
“…Lambert, Larcker, and Baker [20] found that executives who are awarded fixed salary lack a direct incentive to promote corporate performance because they do not share in the resulting gains in the firm's value. Nourayi and Mintz [16] reported that accountingbased measures of performance are positively correlated with executives' cash compensation.…”
Section: Corporate Performancementioning
confidence: 99%